1984
DOI: 10.1148/radiology.150.1.6316416
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic tumors: magnetic resonance and CT appearance.

Abstract: The magnetic resonance (MR) features of primary and metastatic hepatic tumors were analyzed and compared with CT findings in 28 patients. MR images were obtained on a 0.35-Tesla superconducting magnet using a variety of spin echo and inversion recovery imaging techniques. The normal liver appeared homogeneous and of moderate intensity. Tumors typically appeared as masses of increased intensity on spin echo images and diminished intensity on inversion recovery images. Tumors had prolonged T1 and T2 times, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

1984
1984
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(29 citation statements)
references
References 0 publications
2
24
0
3
Order By: Relevance
“…MR1 plays an important role in detecting and differentiating hepatic tumors [18,19]. A number of studies have suggested that FNH can be successfully differentiated from other liver tumors by virtue of isointensity on T1-WI and/or T2-W1, homogeneity, and a central scar which becomes hyperintense on T2-WI [3].…”
Section: Discussionmentioning
confidence: 99%
“…MR1 plays an important role in detecting and differentiating hepatic tumors [18,19]. A number of studies have suggested that FNH can be successfully differentiated from other liver tumors by virtue of isointensity on T1-WI and/or T2-W1, homogeneity, and a central scar which becomes hyperintense on T2-WI [3].…”
Section: Discussionmentioning
confidence: 99%
“…In the mid-1980s, MRI had been reported as an efficient diagnostic tool for liver tumors [10], but only conventional spin-echo sequences with a lengthy acquisition time were available in the clinical setting. By the early 1990s, rapid acquisition sequences that allowed whole liver scanning during breath holding became available and gadolinium-enhanced dynamic MRI of the liver began to be used in daily radiologic practice [11].…”
Section: History Of Radiologic Diagnosis Of Hccmentioning
confidence: 99%
“…To our knowledge, few reports have been published about MR imaging of hepatic adenomas [3][4][5]. Moss et al [3] reported two cases of hepatic adenomas that were hyperintense on long TR/TE pulse sequences on a 0.…”
Section: Discussionmentioning
confidence: 99%
“…Moss et al [3] reported two cases of hepatic adenomas that were hyperintense on long TR/TE pulse sequences on a 0. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation